Performance and emission characteristics of engine using Naviculla Sp. algae oil methyl ester with MgO nanoparticles. (2020) - Arunprasad, J.; Elango, T.
Abstract: Standard diesel fuels have developed the application in several domains like agriculture, transportation as well as commercial sectors performing due to its reduced specific fuel consumption and hydrocarbon emissions. In the present research, the biodiesel from Naviculla Sp. algae oil was prepared by transesterification process, and essential material and chemical properties were measured. The performance and emission characteristics of single cylinder Diesel engine fueled with Naviculla Sp. algae oil methyl ester and its diesel blends with MgO nano additives of B20, B20 + 25 ppm, B20 + 50 ppm B20 + 100 ppm on a volume basis were evaluated with the variation of load and compression ratio. The chemical as well as physical properties of NAME [Naviculla algae methyl ester] blends with MgO nano additives are determined and compared to fulfill the ASTM standards. The empirical outcomes expose that the use of biodiesel with nano-additives in compression ignition engine has revealed the improve in engine performance and reduction in exhaust emissions.